Vale Ferreiro (Fafe). Memória de um lugar da idade do bronze do noroeste português - Sampaio, Hugo Teotónio Pinho Aluai Gonçalves (2018)
The archaeological site of Vale Ferreiro is located at Godarilhas, parish of Serafão, council of Fafe, district of Braga (North of Portugal). It occupies a little hill positioned in the West end spur of Serra da Cabreira’s foothills. Its discovery occurred in 1999, during the opening of a dirt road cutting the plain top of the hill. This situation lead to the implementation of archaeological excavation works in order to safeguard the record of all evidences. The importance of the place turn it in a reference of the Portuguese North-western regional Bronze Age. As such, the necessity of compiling the recovered data helped to its inclusion, more recently, in a Doctoral thesis developed by the rst author of the present work. At a rst time and during the archaeological works, the detection of a tumulus lead to deepen the site research. It was necessary to identify and delimit other eventual new structures, to understand if the set of structures was positioned nearby an residential area, to check any relations of continuity or discontinuity between the identi ed structures and, posteriorly, to try to understand the diachronic occupational dynamic of the place, that is, its biography. Generally, it were identi ed four sepulchral structures, two of which denouncing a high architectural investment without parallels in the region. Along that, a series of structures excavated in the bedrock dating back to the regional Bronze Age, such as pits and post holes, were also detected. Among those structures it must be highlighted pit number 9, whose articulation with twelve post holes evidences a hypothetical different kind of function when compared to the remaining. Along with evidences of a signi cant occupation of the place due to a suggestive set of structures, a group of radiocarbon dates related to different contexts allowed to de ne four phases of occupation dating back to the regional Bronze Age. This fact, associated to unequivocal evidences of funerary practices made Vale Ferreiro a site of substantial interest to better comprehend Bronze Age communities, denouncing a diachronic occupation perpetrated for about one millennium. Keywords: funerary practices; tombs; offerings; diachronic occupation; biography of place; deathscape.